Apparatus and process for energy self-sustainable and high-yield conversion of acid gases (H2S and CO2) into syngas - Massimo Barbieri; Flavio Manenti (Invention Disclosure)
H2S and CO2 are two well-known emissions with cumbersome management and not yet established bulk utilization plans. The invention converts H2S and CO2 in syngas and, as the only by-products, elemental sulphur and water by means of a dedicated (i) Regenerative Thermal Reactor (RTR) and (ii) Acid Gas to syngas (AG2S) process layout thanks to the overall reaction: 2 H2S + CO2 = H2 + CO + S2 + H2O. The reaction is globally endothermic, but it can energetically supplied in situ thanks to a minor injection of oxygen/air. The oxygen injection generates the exothermic reaction S + O2 = SO2 in an appropriate amount so as to achieve and preserve the optimal conversion temperature. The SO2 generated for energy sustainability is therefore converted within the process layout. The once-through conversion is 75%v for the H2S and 50%v for the CO2. The unreacted reactants are split from the syngas and by-products and recycled upstream for complete conversion. The invention is the first process utilizing no sources, neither bio nor fossil, but only emissions to generate syngas and, hence, hydrogen. Two moles of syngas are obtained every three moles of emissions, also achieving the total neutralization of H2S and a relevant cut of CO2. Technology development has reached out the industrialization level. The laboratory testing has been developed in Politecnico di Milano, at the facilities of the Center for Sustainable Process Engineering Research (SuPER); the bench-scale tests have been exerted at the Sotacarbo Sustainable Energy Center SpA facilities and the industrial application is just started at Itelyum Regeneration srl, an ecorefinery for exhausted oil recovery.